2016
DOI: 10.1208/s12248-016-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Small Interfering RNA to Inhibit Vascular Endothelial Growth Factor in Zebrafish Using Natural Brain Endothelia Cell-Secreted Exosome Nanovesicles for the Treatment of Brain Cancer

Abstract: Although small interfering RNA (siRNA) holds great therapeutic promise, its delivery to the disease site remains a paramount obstacle. In this study, we tested whether brain endothelial cell-derived exosomes could deliver siRNA across the blood-brain barrier (BBB) in zebrafish. Natural exosomes were isolated from brain endothelial bEND.3 cell culture media and vascular endothelial growth factor (VEGF) siRNA was loaded in exosomes with the assistance of a transfection reagent. While fluorescence-activated cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(99 citation statements)
references
References 51 publications
1
98
0
Order By: Relevance
“…For example, several published reports have demonstrated that exosomes are capable of crossing the blood-brain barrier (BBB) when active neuroinflammation is present. [47][48][49] Neuroinflammatory cascades often result in the compromised integrity of the BBB, thereby allowing for large macromolecules and even cells to enter from the periphery. 50,51 In addition, some methods of manufacturing and labeling MEX use extended processing times, which may decrease their resulting functional properties.…”
Section: Mex Biodistributionmentioning
confidence: 99%
“…For example, several published reports have demonstrated that exosomes are capable of crossing the blood-brain barrier (BBB) when active neuroinflammation is present. [47][48][49] Neuroinflammatory cascades often result in the compromised integrity of the BBB, thereby allowing for large macromolecules and even cells to enter from the periphery. 50,51 In addition, some methods of manufacturing and labeling MEX use extended processing times, which may decrease their resulting functional properties.…”
Section: Mex Biodistributionmentioning
confidence: 99%
“…Exosomes are a sub-population of specialized membranous extracellular vesicles derived from endocytotic compartments, are 30 to 100 nm in size, and are actively secreted by almost all cell types [95]. The exosomes ability to cross the BBB has been studied in zebrafish and mouse models [96,97]. Only exosomes isolated from brain endothelial cells could cross the BBB and deliver cargo into the CNS suggesting potential homo-tropism for the tissue of origin [97].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%
“…The exosomes ability to cross the BBB has been studied in zebrafish and mouse models [96,97]. Only exosomes isolated from brain endothelial cells could cross the BBB and deliver cargo into the CNS suggesting potential homo-tropism for the tissue of origin [97].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%
“…In addition, a recent study has used the zebrafish embryo model for testing their potential in drug delivery. 115,116 Although preliminary, these studies suggest that the zebrafish embryo could be a very useful model for studying the biology of exosomes in the near future.…”
Section: Outstanding Open Questionsmentioning
confidence: 98%